(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate perfusion index as a predictor of hypotension following spinal anesthesia for caesarean section. Research methods: Studying ninety pregnant women with full-term parturients, aged 18- 40 years old belonging to ASA physical status I-II, having singleton pregnancy undergoing caesarean section under spinal anesthesia. Investigation the variation of perfusion index and mean arterial blood pressure at the study time points after spinal anesthesia. Results: The average perfusion index at all times of the study was both greater than 3 and less than 5. Perfusion index before spinal anesthesia and hypotension after spinal anesthesia had a significant, strong, negative correlation, statistical. The cut-off point of perfusion index in predicting hypotension after spinal anesthesia for cesarean section was 3.45 with a sensitivity of 76% and a specificity of 58%. Conclusion: Perfusion index is valuable to early predict of hypotension following spinal anesthesia for cesarean section.